Perbedaan Prestasi Belajar Antara Mahasiswa Yang Ikut Serta Dan Yang Tidak Ikut Serta Pada Himpunan Mahasiswa (Hima) Teknik Sipil Di Jurusan Teknik Sipil Fakultas Teknik Universitas Negeri Jakarta - Nur Dewi Ratih; Dadang Suyadi; Santoso Sri Handoyo (LPPM Universitas Negeri Jakarta, 2013)
The objective of this study to know there is do not it him difference of learning achievement between students who participate and who did not participate in Student Association Hima in the Departement of Civil Engineering Faculty of Engineering, State University of. The place of research at Departement of Civil Engineering Faculty of Engineering, State University of Jakarta in June-July 2012.This research uses survey methods with documentation.. The sample in this study a number of 60 students. The result of the research is found the difference of learning achievement between students who participate and who did not participate Hima in Civil Engineering. Matter of this means deciphrable research result that learning achievement from students who participate better than students who did not participate Hima in Civil Engineering